Ethos empresarial na prescrição do trabalho: discursos do poder em manuais de integração - Borim, Rosiléia Aparecida (2006)
Nowadays, one of the things most often seen in big companies is executives and managers searching the perfect client services. In order to achieve this objective, corporations invest in training their employees, as their conduct reflects the company s image. In this sense, this work paper, originated from a personal demand, aims at understanding how the company s ethos in the interaction with the employee is built, through the Integration Manuals of a hotel. These Manuals that comprise our corpus are supplied as a guide to the employees entering the company, determining how they should be, do, walk, speak, act and look during work. As noted, through working writings, these Manuals try to anticipate the possible answers, attitudes e situations which may arise during the performance of their activities. Although this research is for a master degree paper, based on the Applied Linguistics area and linked to the research line Speech and Work (Group Atelier), the first part of this paper is dedicated to providing a general overview of the beginning of worldwide hotel and tourism activities. Subsequently, a summarized profile of the concerning company, as related to the way it s structured regarding personnel and types of guests it works with, will be provided. In addition, we will describe how the service standardization process was carried out, which developed into the Manuals. To answer our research question, speech, work and power studies will be employed. As theoretical assumptions of the speech studies, the scenography notions (Maingueneau, 1997,2002) and all their constitutive analysis categories, such as: personal marks (ibidem); topography and chronography (ibidem); modalities (Cervoni, 1989) will be used and, in the case of this research, negation will also be considered (Ducrot, 1987). Another notion used will be ethos (Maingueneau, 1997,2002). In the work studies, as regards to the ergonomy, speech and work notions of Boutet (1993, 1998) will be used to discuss the different speech manifestations in the professional context, and Daniellou (2002), to grasp the different prescription levels present in work. As regards to ergology (Schwartz, 1998,2000), the notions of value conflict and debate , uses of self by self and by others will be discussed, allowing us to observe how the Manuals, in this company, build the idea of employee, in other words, how this employee is understood and/or viewed. As to the power study, the studies developed by Foucault (1997) will be employed, once we will discuss the different ways de instituting power through the written language present in the Manuals. The methodology adopted for this work paper arises from the discourse analysis of the Manuals. The analyses will be carried out based on the articulation among the speech, power and work studies categories. These articulations allowed us to reach the following conclusions: (a) the several procedures used by the enunciator to interact with its co-enunciator; (b) the multiple functions assigned to the speakers; (c) the presence of physical, cognitive and psychical workload, (d) the employee in this company is seen as a passive subject, without voice; (e) the organizational perspective shifts in the opposite direction of ergonomy, that is to adapt work to man and not man to work; (f) the many manifestations of cognitive, social and instrumental language/speech in work; (g) different ways of power construction, e (h) different levels of prescriptions present in work